Metropolis? Ne bi, hvala! - Stanković, Peter (Družboslovne razprave, 2018)
In the article, representations of Ljubljana in Slovenian feature films made during the period of accelerated modernisation from the end of WWII to 1969 are analysed. Semiological analysis shows that Ljubljana is in these films constructed in a rather diverse yet not entirely arbitrary manner, as in all cases various signifiers of modernisation are presented in negative contexts. In films, where signs of modernisation are largely absent, Ljubljana appears as pleasant and beautiful city, whereas in films, where signs of modernisation are present, Ljubljana is presented as neurotic and alienated city. These representations could be explained by the relatively low status of urbanity in Slovenian culture.
Keywords: Modernisation; Modernizacija; Slovenian motion pictures; Slovenski film; Urbanizacija; Urbanization